Analisis Penggunaan Media Pembelajaran Interaktif di Sekolah Dasar Wilayah 3T Kabupaten Gorontalo Utara - Pakaya, Idan I.; Djahuno, Ridwanto; Imran, Fitrian; Mahmud, Ratna; Kai, Nurlela (Ideas Publishing, 2024)
The use of learning media in schools is important to be implemented in order to provide relevant and effective learning in the midst of very rapid technological developments. This study aims to analyze the use of interactive learning media in 3T Elementary School in North Gorontalo Regency. The method used is quantitative with observation data collection techniques, questionnaires and documentation. The results of the study showed that SD Negeri 3 Tomilito with a percentage of 84.33%, SD Negeri 6 Monano 82.33%, SD Negeri 8 Anggrek 84.66% and SD Negeri 6 Anggrek with a percentage of 85%. Thus, the use of interactive learning media in 3T elementary schools in North Gorontalo Regency has a positive impact on student learning outcomes.